2022
DOI: 10.1111/tid.13834
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre‐transplant bloodstream infection on clinical outcomes after heart transplantation

Abstract: Background: Active bloodstream infection (BSI) is a contraindication for heart transplantation (HT). However, some critical patients with BSI may undergo HT as a lifesaving procedure. We aimed to investigate the impact of pre-transplant BSI on the clinical outcomes after HT. Methods:We enrolled 511 consecutive patients who underwent HT between 1999 and 2019. Patients were divided into two groups based on the presence of BSI within 30 days preoperatively. Forty-three patients (8.4%) with BSI who were clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Infection remained the leading cause of mortality in both groups in this study. Our previous research found that post-transplant dialysis and early bloodstream infection contributes to a 5.5-fold and 3.43-fold increase in early mortality, respectively [ 18 , 21 ]. In the present study, the PCCS group exhibited a higher incidence of certain factors, namely, post-transplant ECMO support (29%), delayed sternum closure (31%), early bloodstream infection (18%), and dialysis (41%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection remained the leading cause of mortality in both groups in this study. Our previous research found that post-transplant dialysis and early bloodstream infection contributes to a 5.5-fold and 3.43-fold increase in early mortality, respectively [ 18 , 21 ]. In the present study, the PCCS group exhibited a higher incidence of certain factors, namely, post-transplant ECMO support (29%), delayed sternum closure (31%), early bloodstream infection (18%), and dialysis (41%).…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, sternal closure may be delayed for 24 h if adequate hemostasis is not achieved. Furthermore, immunosuppressant and desensitization protocols were followed as usual, based on previous publications [ 18 21 ].…”
Section: Methodsmentioning
confidence: 99%